Obstetric care of women with female genital mutilation attending a specialized clinic in a tertiary center. Issue 2 (9th October 2015) - Abdulcadir, Jasmine; Dugerdil, Adeline; Yaron, Michal; Irion, Olivier; Boulvain, Michel
Abstract: Objective: To study the obstetric outcomes of women attending a specialized clinic for women with female genital mutilation (FGM). Methods: The medical charts of women with FGM who consecutively attended a specialized clinic between 2010 and 2012 were reviewed retrospectively. The present study focused on women attending for obstetric reasons. The outcome measures were type of delivery, reason for cesarean delivery or assisted delivery, blood loss, episiotomy, perineal tear, duration of the second stage of labor, postpartum complications, weight of the neonate, and Apgar score. Outcomes were compared between women with FGM type III who underwent defibulation, and patients with FGM type I and II. Results: The clinic was attended by 129 women, 84 perinatally. Obstetric outcomes were similar to average outcomes for women without FGM presenting at the same department and in Switzerland generally. Specifically, 20 women had a cesarean delivery. An assisted delivery was performed for 18 patients; among these, only eight had experienced obstructed labor. No statistically significant differences were found for the outcome measures when women with FGM type III were compared to FGM type I and II. Conclusions: Routine obstetric follow‐up combined with specialized care for women with FGM, including defibulation, can avoid inappropriate obstetric practices and reduce obstetric complications known to be associated with FGM.